Palladium-Catalyzed Cross-Coupling of 1,3,4-Oxadiazoles and Styrenes: An Efficient Method to Synthesize 2-Alkenyl-1,3,4- Oxadiazoles§ - Salvanna, N.; Reddy, P. Raghavendar; Das, Biswanath (Synlett, 2018)
2-Alkenyl-1,3,4-oxadiazole derivatives have been prepared by cross-coupling of 1,3,4-oxadiazoles with styrenes by using palladium(II) trifluoroacetate [Pd(TFA)2] as a catalyst, 1,10-phenanthroline as a ligand, silver trifluoroacetate as an oxidant, and toluene as a solvent. The products were formed in high yields and no byproducts were detected.
Keywords: oxadiazoles; styrenes; palladium catalysis; cross-coupling; silver trifluoroacetate; alkenylation